Determinação do teor de NaCl, Glicose e KCI em medicamentos injetáveis por fotometria usando exploração do efeito Schlieren em Sistemas FIA e PLS1 - Diniz, Paulo Henrique Gonçalves Dias (2010)
This study evaluated using the Schlieren effect in FIA systems as a new strategy to determine the amounts of sodium chloride, potassium chloride and glucose, each respectively in intravenous drugs. The proposed methodology was based on the difference between the refractive indices of sample zones and the carrier stream. With this perspective, photometric detection was used based on an LED and a phototransistor to investigate the different analytical profiles related to the Schlieren effect in low flow rate conditions. Adjustment studies of the parameters and flow settings (which were most suitable to exploit Schlieren profiles), were performed. The proposed methodology generates a large amount of chemical information and therefore requires the use of chemometric tools. Data evaluation was performed with the application of a partial least squares regression (PLS1), employing the standard solutions of each analyte to construct and validate the models. The models were then used to predict the content of each analyte in their real samples. The results demonstrated the predictive ability of the constructed PLS1 models, and the predicted concentration values were in agreement with the reference values, with 95% of confidence. The main advantages of using the Schlieren effect in the chemical analysis is that no reagent is employed, low volumes of samples are used and no expensive radiation detectors are used.